Rational–Ethical Drivers and Sharia Compliance Dynamics in Hasanah Card Usage within Manado’s Multicultural Banking Environment - Syarifuddin, Syarifuddin; Suna, Laila (UIN Sunan Gunung Djati, 2026)
This study aims to analyze the motivations, perceptions, and lived experiences of both Muslim and non-Muslim users of the Hasanah Card, as well as to evaluate the effectiveness of its sharia compliance mechanisms within the multicultural social context of Manado, North Sulawesi. This research is driven by the increasing use of sharia-based financial products by non-Muslims, indicating the need for a renewed understanding of the universality of sharia values and the limits of their implementation in plural public spaces. The study employs a descriptive qualitative method through semi-structured interviews with Hasanah Card users and officers of Bank Syariah Indonesia (BSI), complemented by limited observation and internal documentation. The findings show that the decision to use the Hasanah Card is primarily shaped by economic rationality—particularly fee transparency, the absence of interest, and a sense of transactional security. For non-Muslim users, sharia is understood not as a religious identity but as a set of universal ethical values—fairness, honesty, and accountability. Regarding compliance, the Merchant Category Code (MCC) mechanism effectively blocks transactions in prohibited merchant categories, yet it faces substantive limitations because it cannot detect non-halal items in mixed merchants. As a result, sharia compliance shifts from a purely technical system to one that depends on individual user ethics. The findings further reveal that non-Muslim use of sharia products occurs without identity-based resistance; sharia is perceived as a shared public value within a multicultural society. This study offers important implications for the development of more inclusive and adaptive Islamic financial products, particularly in strengthening compliance system design, ethical literacy, and communication strategies that position sharia as a universal ethical framework. The study’s originality lies in its identification of hybrid rationality and its mapping of the gap between formal and substantive compliance—an area that remains understudied in Indonesian Islamic finance literature.